2014
DOI: 10.4172/2157-7595.1000178
|View full text |Cite
|
Sign up to set email alerts
|

A Study to Identify the Benefits, Barriers, and Cues to Participating in a Yoga Program among Community Dwelling Older Adults

Abstract: Benefits of physical activity Physical activity plays an important role in the treatment of chronic diseases in older adults. Physical activity has beneficial effects for the treatment of cardiovascular disease, high blood pressure, high cholesterol, chronic lung disease, diabetes, obesity, and osteoarthritis. These beneficial effects occur in people of all ages, including the 65 and over population. Physical activity also helps to relieve symptoms of depression, helps to maintain independent living, and enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…These results can be explained by a good working environment that promotes the empowerment of employees which is more likely to "gain" their trust. 23 In addition, Nayak et al 24 found that the willingness of the participants to do yoga depended on their perception of benefits and barriers. Therefore, the workers had good risk judgment or decision making in their capacities which was related to sociopsychological theory of decision making to individual health related behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…These results can be explained by a good working environment that promotes the empowerment of employees which is more likely to "gain" their trust. 23 In addition, Nayak et al 24 found that the willingness of the participants to do yoga depended on their perception of benefits and barriers. Therefore, the workers had good risk judgment or decision making in their capacities which was related to sociopsychological theory of decision making to individual health related behaviors.…”
Section: Discussionmentioning
confidence: 99%